Factors of entrepreneurial business success: towards resilient and competitive entrepreneurs in the post covid-19 pandemic era - Maheran Zakaria,; Indrawati Yuhertiana,; Dedi Muhammad Siddiq,; Dwi Suhartini,; Rabaatul Azira Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The COVID-19 pandemic has tremendously affected the economy, business, and human life, especially for micro entrepreneurs in the low-income bracket. In fact, many have yet to achieve success in the aftermath of the pandemic. Drawing from Social Cognitive Theory and existing literature, this study aimed to investigate self efficacy, digital adoption, social persuasion, and passion for work as factors influencing entrepreneurial business success, with self-efficacy proposed as a mediator of the relationships between the other factors and entrepreneurial business success. Employing a cross-sectional survey technique, a questionnaire was distributed via email to 250 micro-entrepreneurs in West Java, Indonesia. Of these, 174 responded, and 160 datasets were suitable for further analysis. Multiple regression results derived from SmartPLS 3 indicate that all the proposed variables significantly influence both self-efficacy and entrepreneurial business success. Moreover, the findings demonstrate that self-efficacy acts as a mediator between the examined factors and entrepreneurial business success. These discoveries offer valuable insights for policymakers, poverty alleviation organizations, and researchers in developing strategies and intervention programs for entrepreneurial business growth. Thus, these findings align with the goals of the Indonesian government and the United Nations' Sustainable Development Goals to cultivate resilient and competitive micro-entrepreneurs, striving towards a zero-poverty nation by 2030.